Evaluating the quality of life in patients with oral cancer: a central Indian cross-sectional study - Wath, Darshan; Wadhva, Sarita; Rathod, Pragati; Narlawar, Uday; Padyal, Pratik; Kumar, Mohit (International Journal Of Community Medicine And Public Health, 2024)
Background: Oral cancer significantly impacts patients' quality of life (QoL) due to its associated physical, emotional, and social challenges. This study aimed to assess the QoL of oral cancer patients in Central India. Method: A cross-sectional study was conducted in 210 oral cancer patients from various healthcare institutions in Central India. Participants completed the UW-QOL questionnaire, which evaluates multiple domains, including pain, appearance, chewing, swallowing, speech, anxiety, mood, taste, activity, saliva, recreation, and shoulder function. Descriptive statistics were used to analyze QoL scores and identify the prevalence of significant issues across domains. Results: The findings revealed that shoulder function had the highest mean score (96.71), with 91.9% of participants achieving optimal scores. Saliva function followed (mean score: 83.62), with 56.2% of subjects at the best score. However, pain (mean score: 59.40) was the most significant issue, reported by 55.71% of patients, alongside notable concerns in appearance (32.38%) and anxiety (23.8%). Other domains, including mood and activity, exhibited low mean scores, with fewer than 15% of subjects reporting optimal scores. Conclusions: This study highlights the disparity in QoL among oral cancer patients in Central India, with pain and chewing emerging as significant challenges. The results underscore the need for targeted interventions to address both the physical and psychosocial aspects of care, enhancing the overall QoL for these patients.